High-temperature strength and microstructural analysis in Si-3/N-4/20-vol%-SiC nanocomposites - Cheong, DS; Hwang, KT; Kim, CS (AMER CERAMIC SOC, 1999)
Si3N4/20-vol%-SiC nanocomposites with Al2O3 and Y2O3 as sintering additives have demonstrated very high strength at room temperature; however, the high-temperature strength was drastically decreased, because of the low softening temperature of the grain-boundary phase. To improve the high-temperature strength, only Y2O3 was used as a sintering additive. Results showed that the fracture strength of this nanocomposite at temperatures >1200 degrees C was increased by adding Y2O3 without Al2O3; however, a distinct decrease in the high-temperature strength still was observed for higher Y2O3 contents, The fracture strength at room temperature (similar to 1 GPa) was maintained up to 1400 degrees C in the sample that contained SiC particles (30 nm in size) and 4 wt% of Y2O3. Remarkably, the SiC particles at the grain boundaries were bonded directly to Si3N4 grains without a glassy phase. This sample fractured in an elastic manner without exhibiting plastic deformation up to 1400 degrees C and showed no evidence of subcritical crack growth on the fracture surface. The significant improvement of the high-temperature strength in this nanocomposite can be attributed to inhibition of grain-boundary sliding and cavity formation, primarily by intergranular SiC particles that are bonded directly to the matrix grains, as well as crystallization of the grain-boundary phase. Rietveld analysis of the X-ray diffraction data revealed the presence of a secondary phase-10Y(2)O(3). 9SiO(2). Si3N4 (h-phase)-in samples with Y2O3, whereas YSiO2N was present in the samples that contained both Y2O3 and Al2O3.
Keywords: SILICON-NITRIDE CERAMICS; HOT-PRESSED SI3N4; MECHANICAL-PROPERTIES; FRACTURE-TOUGHNESS; PHASE; BEHAVIOR; SYSTEM; GLASS; SIZE; ADDITIVES